PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATERI POKOK SUHU DAN KALOR DI KELAS X SEMESTER II SMA NEGERI 11 MEDAN T.P. 2015/2016 - Harahap, Syahrizal; Siregar, Alkhafi Maas (JURNAL IKATAN ALUMNI FISIKA UNIVERSITAS NEGERI MEDAN, 2017)
This research is aimed to investigate the effect of problem-based learning (PBL) on student s learning outcome in heat temperature topic in the second semester of grade X SMA Nil Medan A. Y. 2015 2016. Ihis research is a quasi experimental population of all class X SMA Negeri 1 I Medan, which consists of ten classes. Samples were taken two classes are determined by random cluster sampling technique . X-9 as the experimental class and class X-10 as the control class . The results were obtained value-average pretest experimental class 24,58 and the control class 22.58. After the study was completed, given the posttest and average values obtained 73.13 experimental class and control class 68,87. It can be concluded that there is a significant influence of problem based learning on students learning outcome in heat temperature m grade X SMA Nil Medan T.P. 2015 2016.